2021
DOI: 10.3389/fonc.2021.714421
|View full text |Cite
|
Sign up to set email alerts
|

GSTT1null and rs156697 Polymorphism in GSTO2 Influence the Risk and Therapeutic Outcome of B-Acute Lymphoblastic Leukemia Patients

Abstract: IntroductionGlutathione S-transferase (GST) gene deletion or polymorphic sequence variations lead to decreased enzyme activity that influences susceptibility and response to chemotherapy in acute lymphoblastic leukemia (ALL). This case–control study investigated the association of GST gene polymorphisms with the etiology and therapeutic outcome of B-ALL among Kashmiri population.MethodsA total of 300 individuals including 150 newly diagnosed B-ALL patients and an equal number of age and gender matched controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
2
2
0
Order By: Relevance
“…Significantly more than 3–times increased risk of ALL in patients has been reported in GSTT1 null and GSTM1 null genotypes. 11 , 16 , 24 Similarly, more than 4–folds increased risk of ALL with combined GSTT1 null and GSTM1 null polymorphisms has also been reported by Baba et al 16 …”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Significantly more than 3–times increased risk of ALL in patients has been reported in GSTT1 null and GSTM1 null genotypes. 11 , 16 , 24 Similarly, more than 4–folds increased risk of ALL with combined GSTT1 null and GSTM1 null polymorphisms has also been reported by Baba et al 16 …”
Section: Discussionsupporting
confidence: 56%
“… 12 , 32 GSTT1 and GSTM1 genetic polymorphisms are associated with loss–of–function mutations that leads to the complete loss of activities of these enzymes. 16 In the present study, GSTT1 and GSTM1 genetic polymorphisms were investigated in newly diagnosed adult patients with ALL in Sudanese population. Several studies have investigated the association of GSTT1 and GSTM1 deletions in patients with acute leukemia with conflicting results.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, cell signaling, post-translational modifications, cell proliferation, differentiation, cellular apoptosis, antiinflammatory, proinflammatory, prevention of DNA damages, and resistance to chemotherapeutic drugs are other non-enzymatic function of GTs (Cerliani et al ., 2016;Singh et al ., 2021). GSTT1 and GSTM1 genetic polymorphisms are associated with loss-of-function mutations that leads to the complete loss of activities of these enzymes (Baba et al, 2021). Most of these finding was compatible with recent studies of (Abdalhabib et al ., 2022 ;Moulik et al ., 2014) Multiple studies have demonstrated that susceptibility to cancer is caused by a deficiency in xenobiotic-metabolism genes (GSTT1 and GSTM1 )were significantly higher in the cases groups compared to the control group (Aziz, 2010) data demonstrated that GST frequent determined in Iraq population GST polymorphism have been related to different cancer some of may be direct associated with cancerogenic toxic factor.…”
Section: Resultssupporting
confidence: 87%
“…In addition, one study (Jiang et al, 2008) was excluded because another publication (Jiang and Tan, 2010) included their cases and controls. Therefore, 87 publications (Zintzaras, 2009;Aydin-Sayitoglu et al, 2006;Al-Achkar et al, 2014;Arruda et al, 2001;Allan et al, 2001;Abdalhabib et al, 2021;Alves et al, 2002;Al-Eitan et al, 2016;Bajpai et al, 2007;Balta et al, 2003;Bhat et al, 2012;Bhatla et al, 2008;Barnette et al, 2004;Bolufer et al, 2007;Baba et al, 2021;Bănescu et al, 2016;Bănescu et al, 2014;Chen et al, 1997;Chen et al, 2008;Crump et al, 2000;Chauhan et al, 2011;Chauhan et al, 2012;Canalle et al, 2004;Clavel et al, 2005;Chan et al, 2011;D'Alò et al, 2004;Davies et al, 2000;Davies et al, 2002;Dunna et al, 2013;Eyada et al, 2007;Feng et al, 2004;Farasani, 2019;Gra et al, 2008;Guven et al, 2015;Haase et al, 2002;Hishida et al, 2005;Haranatha Reddy and Jamil, 2006;Idris et al, 2020;Jiang and Tan, 2010;…”
Section: Study Characteristicsmentioning
confidence: 99%